Use of metformin and risk of breast and colorectal cancer. (July 2020) - Rennert, Gad; Rennert, Hedy S.; Gronich, Naomi; Pinchev, Mila; Gruber, Stephen B.
Abstract: Background: Diabetes has been associated with increased risk of cancer, including breast cancer and colorectal cancer. Metformin, an oral hypoglycemic drug, but not other anti-diabetic drugs, has been associated with reduced risk of breast and of colon cancers in some, but not in other, studies. Methods: Data from two large-scale, population-based, case-control studies of breast and colorectal cancers etiology, conducted in Northern Israel since 1998 were analyzed to evaluate the association between regular use (>3 times) of metformin prior to diagnosis and risk of developing cancer. The multivariate analyses for both cancer sites included age, family history of breast/colorectal cancer, history of diabetes, sports participation, fruits/vegetables consumption, aspirin and statins use, and for breast cancer, also included use of oral contraceptives and postmenopausal hormones and number of pregnancies. Use of metformin and diabetes status were determined based on valid electronic medical records of the participants. Results: Metformin use prior to diagnosis of cancer was associated with a decrease in risk of both breast cancer (OR = 0.821, 0.726–0.928, p = 0.002) and colorectal cancer (OR = 0.754, 0.623–0.912, p = 0.004). An inverse association was not identified with use of other anti-diabetic medications. Diabetes was found to be associated with risk of colorectal cancer (OR = 1.204, 1.014–1.431, p = 0.034) but not of breast cancer. No dose response by years of use of metformin was found. Conclusion: These analyses of large population-based studies provide evidence of a strong inverse association of metformin with breast and, even more so, with colorectal cancer risk.